Kajian Literatur: Hambatan Implementasi Asesmen Kompetensi Minimum (AKM) Literasi Numerasi di Sekolah Menengah Pertama - Tiska Dwi Amelia; Lidiana Fitria Ningsih; Tri Wahyuni; Ulfia Churidatul Andriani (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
This study aims to identify barriers in the implementation of Minimum Competency Assessment (AKM) in literacy and numeracy at the junior high school level through a literature review of 20 relevant articles. The method used was a Systematic Literature Review with stages of searching, selecting, extracting, and synthesizing data. The results of the study show that the main obstacles to AKM include: (1) teacher obstacles, in the form of a lack of understanding of the concepts and indicators of AKM and a lack of contextual practice questions; (2) student barriers, in the form of low ability to understand texts, interpret data, choose solution strategies, and lack of accuracy; and (3) infrastructure barriers, such as limited technological devices, teaching materials, and literacy environments. These findings confirm that the success of AKM depends on the readiness of the overall education ecosystem, not just the technical aspects of assessment. The results of this study can be used as a basis for teachers, schools, and policy makers in strengthening the implementation of AKM in junior high schools.